2009
DOI: 10.1159/000254903
|View full text |Cite
|
Sign up to set email alerts
|

Group Psychotherapy of Dysfunctional Fear of Progression in Patients with Chronic Arthritis or Cancer

Abstract: Background: This study investigated the effectiveness of brief psychotherapeutic group interventions in reducing dysfunctional fear of disease progression (FoP). The interventions comprised either cognitive-behavioral group therapy or supportive-experiential group therapy. We tested whether these generic interventions would prove effective in different illness types. Methods: Chronic arthritis in- patients (n = 174) and cancer in-patients (n = 174), respectively, were randomized to receive one of the two inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
98
0
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(112 citation statements)
references
References 92 publications
2
98
0
9
Order By: Relevance
“…The anxiety scores were strikingly low in all 3 of the applied questionnaires. The fear of cancer progression (FoP-Q) was lower, as has also been demonstrated in other cancer patient groups [12,13]. Only 17% of the patients had clinically elevated scores of PTSS-10, whereas in the study of Einsle et al [14] 30.9% of the cancer patients were within this range.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The anxiety scores were strikingly low in all 3 of the applied questionnaires. The fear of cancer progression (FoP-Q) was lower, as has also been demonstrated in other cancer patient groups [12,13]. Only 17% of the patients had clinically elevated scores of PTSS-10, whereas in the study of Einsle et al [14] 30.9% of the cancer patients were within this range.…”
Section: Discussionmentioning
confidence: 57%
“…We measured anxiety using a psychometric tool for the physically ill, and also assessed the fear of cancer progression and posttraumatic stress. Fear of progression has been studied in cancer and other chronically ill patients [11,12]. Using the Fear of Progression Questionnaire (FoP-Q), patients with rheumatoid arthritis were found to present significantly higher values compared to cancer patients, while in stroke patients the fear of progression was significantly lower [13].…”
Section: Introductionmentioning
confidence: 99%
“…Pre-treatment evaluation of subclinical depressive symptoms may help to detect patients at risk who might benefit from interventions tailored to specific problems such as FCR. 7,38 Fear of cancer recurrence (FCR) in patients with hematological cancers S Sarkar et al…”
Section: Discussionmentioning
confidence: 99%
“…FCR is defined as the fear or worry that cancer will return, progress or metastasize. [3][4][5][6][7] FCR is often conceptualized as a multidimensional phenomenon, including emotional components of anxiety and fear, and a cognitive dimension, including worry, preoccupation and intrusive thoughts. 3,8,9 Prevalence estimates of FCR range between 22 and 99% among cancer survivors and FCR is considered to be one of the most distressing psychological consequences of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that arthritis patients worry about the future, especially about the long term medication use and their prognosis, due to the unpredictable course and the varying disease activity (151)(152)(153)(154). To our knowledge no previous studies have reported patients' concerns about the availability and potential risks of future treatments.…”
Section: ] If You Have Little Information There's Little To Worry Amentioning
confidence: 99%